Severe liver injury induced by minocycline in hepatitis B patient: a Case Report - Wang, Ran; Li, Yun; Xia, Xue (Frontiers in Pharmacology, 2024)
Physical liver injury is an acute and potentially serious adverse event that may result in acute liver failure or even death. Diagnosis is often challenging. Minocycline, a semi-synthetic second-generation tetracycline, has high fat solubility and good tissue permeability. It is widely used for acne treatment. This report presents a 32-year-old female hepatitis B carrier who took minocycline (50 mg twice daily) for acne. After 1 week, she experienced fatigue, jaundice, abdominal bloating, and discomfort. Upon admission, laboratory tests revealed significantly elevated transaminase levels, ascites on abdominal ultrasonography, positive hepatitis B markers, impaired coagulation function, and a final diagnosis of subacute liver failure with chronic hepatitis B. Following discontinuation of minocycline and initiation of liver enzyme protection therapy, the patient’s liver and coagulation functions improved after undergoing artificial liver therapy combined with CRRT. This case highlights a rare occurrence of minocycline-induced liver injury in a hepatitis B carrier, emphasizing that acute liver injury is a potential and serious adverse effect of minocycline, particularly in patients with pre-existing liver disease.